Pengaruh Manajemen Kelas Make Every Minute Count Terhadap Keaktifan Belajar Siswa Kelas IV di Madrasah Ibtidaiyah Taufiqurrahman 2 Kukusan - Hermawan, Cecep Maman Hermawan; Siti Nur Elizah; Rosfiani, Okta (Tarunateach: Journal of Elementary School, 2024)
This study aims to find out: (1) Population variance of the two groups is the same or homogeneous, (2) Differences in average student learning outcomes, (3) The influence of class management Make Every Minute Count on student learning activity. This research is quantitative research using experimental methods and quasi-experimental design. The research population is the entire student at MI Taufiqurrahman 2 Kukusan which totaled 457 students. The sample technique used is purposive sampling. Research sample of 42 students consisting of class IV A 21 students (experimental) and IV B 21 students (kontrol). The data collection technique uses the lift as the primary instrument. From the test results the instrument obtained a Table R of 0.396 and Cronbach's Alpha of 0.836. The results analysis technique uses the t-test, which compares the two groups' mean. The research findings indicate that: (1) Based on the information available, the significance level (Sig.) is less than 0.198 > 0.05, indicating a similar or homogenous population variation. (2) Based on results showing that the average learning time for the Afterwards Experiment (Make Every Minute Count) was 86,00 and the average deviation was 5,167, as well as the Average Learning Time for the Afterwards Control (Classroom Meeting) was 82,29 and the average deviation was 6,133. It may be observed that there are differences in student learning activity between the "Make Every Minute Count" and "Classroom Meeting" lesson plans. (3) Based on the Uji Wilcoxon results, Asymp.Sig. (2-Tailed) 0,000 < 0,05 or Ha is found. Thus, it is shown that there is a difference in the Make Every Minute Count staff's learning activity among fourth-grade students.